ENHANCING FIRM VALUE: ANALYZING INTELLECTUAL CAPITAL, CAPITAL STRUCTURE, AND PROFITABILITY IN INDONESIA - Priyanto, Panji; Tias, Putri Wahyuning; Suhandi, Ni Putu Mila (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
This study investigates the impact of Intellectual Capital (IC), Capital Structure (CS), and Profitability (PR) on Firm Value (FV), with profitability acting as a mediating variable. Utilizing a quantitative approach, secondary data from 190 observations of consumer goods companies listed on the Indonesia Stock Exchange (IDX) were analyzed through SmartPLS. Companies experiencing losses or conducting IPOs during the research period were excluded. Firm value was proxied by Return on Assets (ROA), a key indicator of a firm's efficiency in generating profits from its assets. IC was measured using the Value-Added Intellectual Coefficient (VAIC), comprising Human Capital Efficiency (HCE), Capital Employed Efficiency (CEE), and Structural Capital Efficiency (SCE). Capital Structure was measured using the Debt-to-Equity Ratio (DER), and profitability was assessed via Price-to-Book Value (PBV). The results revealed that Intellectual Capital significantly enhances both profitability and firm value, highlighting the role of intangible assets in firm performance. Capital Structure exhibited a negative direct effect on firm value but positively influenced profitability. Profitability, in turn, had a strong positive effect on firm value, underscoring its mediating role in the relationship between IC, CS, and FV. These findings emphasize the importance of effective management of intellectual and capital resources in maximizing firm value in the consumer goods sector in Indonesia